IMPLEMENTASI PERDA KABUPATEN BENGKALIS NO. 07 TAHUN 2006 (IZIN PENGELOLAAN DANPENGUSAHAANSARANG BURUNG WALETDI KECAMATAN BENGKALIS KABUPATEN BENGKALIS) - Kurniawan, Rizki; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
License Management and exploitation of Swallow Nest issued by the Government of Bengkalis is for taken any action against employers of bird's nest in order to create orderly administration and compliance business owners against the rules set by the district government Bengkalis and pay a fee for permission as one income The original area. Therefore Bengkalis Government issued a Local Regulation No. 07 Year 2006 on Management and Exploitation of Swallow's Nest. This study aims to determine Implementation Management and Operation License Swallow's Nest in the District of Bengkalis and to determine the factors that affect the implementation License Management and Exploitation of Swallow's Nest in District Bengkalis. In a theoretical model of implementation by Edward III, there are four variables that influence the implementation policy, namely: communication, resources, disposition or attitude of execution, as well as bureaucratic Structure.The method used in this study is a qualitative study. With the technique done of snowball sampling, the key informant in this study. In this study, the informant is the Department of Forestry and Integrated Licensing Service Agency, Entrepreneur Swallow's Nest and Society in the District of Bengkalis. Then analyzes the data and manage.The study found that the Implementation License Management and Exploitation of Swallow's Nest in the District of Bengkalis has not undone the fullest. This is evidenced still a lot of bird's nest entrepreneurs who do not have permissions Management and Operation Swallow's Nest. Factors affecting Implementation Management and Operation Permit Swallow's Nest in the District of Bengkalis includesinternal factors, lack of socialization, supervision and strict sanctions from the implementor against employers who violate the Regulation, External factors here happens because of lack of awareness of the people or entities that perform management and exploitation of bird's nest on the importance of management and exploitation license swallow nest.Keywords: Implementation, Local Regulation, Licence Management and Exploitation of swallow's nests